2008
DOI: 10.1039/b809441a
|View full text |Cite
|
Sign up to set email alerts
|

Spatial metabolic fingerprinting using FT-IR spectroscopy: investigating abiotic stresses on Micrasterias hardyi

Abstract: The release of active pharmaceutical ingredients (APIs) into the environment is an ecologically important topic for study because, whilst APIs have been designed to have a wide range of biological properties for the target of interest (usually in man), little information on potential ecological risks is currently available regarding their effects on the organisms that inhabit the environment. In this study, the algae Micrasterias hardyi was exposed to propranolol, metoprolol (beta-adrenergic receptor agonist d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…N-H bending of peptides and proteins45 . Details of the affected FT-IR bands and their corresponding assignments are provided inTable S2.…”
mentioning
confidence: 99%
“…N-H bending of peptides and proteins45 . Details of the affected FT-IR bands and their corresponding assignments are provided inTable S2.…”
mentioning
confidence: 99%
“…For instance, FT-IR spectroscopy has proved sensitive enough for analysis of the chemical composition of a single strain of Escherichia coli after exposure to ionic liquids (6), for functional genomics screening (22), for measuring abiotic perturbations in algae (39), and for characterization of microbial degradation pathways (16). We believe that this technique offers considerable potential for rapid differentiation of metabolic changes of bacteria responding to contrasting growth regimes in natural and engineered environments, although this remains to be demonstrated.…”
mentioning
confidence: 99%
“…Previous studies have suggested that ␤-blockers do not affect microbes due to the absence of the API receptors in these organisms (10,23). However, in another study conducted by our group we reported that (Ϯ)-propranolol significantly reduced the amount of lipid storage components of the alga Micrasterias hardyi 649/15 and caused a marked reduction in the cellular protein content (34). In addition, the findings obtained by metabolic fingerprinting suggested that the phenotype was altered during exposure to this API (34).…”
Section: Vol 76 2010 Effects Of Pharmaceuticals On Aquatic Microorgmentioning
confidence: 60%
“…However, in another study conducted by our group we reported that (Ϯ)-propranolol significantly reduced the amount of lipid storage components of the alga Micrasterias hardyi 649/15 and caused a marked reduction in the cellular protein content (34). In addition, the findings obtained by metabolic fingerprinting suggested that the phenotype was altered during exposure to this API (34). To our knowledge, no further studies on the metabolic effects of propranolol in aquatic microorganisms have been carried out.…”
Section: Vol 76 2010 Effects Of Pharmaceuticals On Aquatic Microorgmentioning
confidence: 94%